SAT0602 INCIDENCE OF INFLAMMATORY ARTHRITIS BEFORE AND AFTER THE INTRODUCTION OF NEW CLASSIFICATION CRITERIA: A SYSTEMATIC REVIEW. (2nd June 2020) - Van Delft, E.; Abdelkadir, M. J.; Den Braanker, H.; Hazes, J.; Lopes Barreto, D.; Weel, A.
Abstract : Background: Hallmark in treatment of inflammatory arthritis (IA); rheumatoid arthritis (RA), axial spondyloarthritis (axSpA) and psoriatic arthritis (PsA), is to treat early with intensive regimens to induce remission and prevent disability on the longer term [1, 2, 3]. To be able to start treatment in an earlier stage of the disease, around a decade ago new classification criteria sets were introduced; 2010 ACR/EULAR for RA, 2009 ASAS for axSpA and 2006 CASPAR criteria for PsA. Compared to old criteria sets for RA, axSpA and PsA these new ones cover a broader spectrum of early disease features [2]. Although classification criteria are not developed for diagnosing, they are widely adopted for use as aids in diagnosing IA [4]. Therefore, the new criteria sets might have led to an increased reported incidence of IA [5]. Objectives: To determine whether the reported incidence of IA has changed after introduction of the new classification criteria this systematic review has been conducted. Methods: A systematic literature search was conducted using Embase, Medline Ovid, Cochrane Central and Web of Science from database inception to September 2019. For this study only articles that addressed the incidence of IA in adult referrals towards the rheumatologist were included (Fig. 1 ). A meta-analysis was performed to compare the pooled estimates and 95% confidence intervals (CI) for the incidence of IA before and after the introduction of new classification criteria. Results: A total of 14 studies reporting on the incidence of RA (n=10), axSpA (n=7) and PsA (n=4) in adults newly referred towards the rheumatologist were included. Pooled incidences were for RA 11% (95% CI 6-15%); for axSpA 4% (95% CI 3-5%); and for PsA 4% (95% CI 3-5%). Graph 1 and 2 show a significant increase in incidence of 9% for RA (p=0.019) and 2% for axSpA (p=0.006) after the introduction of the new classification criteria for respectively RA and axSpA. For PsA only one study was included reporting on the incidence of PsA in rheumatology centres before 2006, hence pooled estimates before and after introduction of new criteria could not be compared. Overall there was a high intragroup heterogeneity (p=0.00) caused by geographical area and study design. Conclusion: Rheumatoid arthritis is the most frequent IA diagnosis in newly referred patients, of which the incidence increased over time up to 15%. The introduction of new classification criteria might have introduced higher incidence rates for IA, although heterogeneity could have influenced the results. References: [1]Monti S, Montecucco C, Bugatti S, Caporali R. Rheumatoid arthritis treatment: the earlier the better to prevent joint damage. RMD Open, 2015. 1 [2]Dubash S, McGonagle D, marzo-Ortega H. New advances in the understanding and treatment of axial spondyloarthritis: from chance to choice. Ther Adv Chronic Dis, 2018. 9(3):77-87 [3]McLaughlin M, Ostör A. Early treatment of psoriatic arthritis improves prognosis. Practitioner, 2014. 258:21-4 [4]Rudwaleit M, Taylor WJ. Classification criteria for psoriatic arthritis and ankylosing spondylitis/axial spondyloarthritis. Best Pract Res Clin Rheumatol, 2010. 24(5):589-604 [5]Van der Linden MPM, Knevel R, Huizinga TWJ, van der Helm-van Mil AHM. Classification of rheumatoid arthritis: comparison of the 1987 American College of Rheumatology criteria and the 2010 American College of Rheumatology/European League Against Rheumatism criteria. Arthritis Rheum, 2011. 63(1):37-42 Disclosure of Interests: None declared